2015
DOI: 10.1007/s00244-015-0163-6
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Residues in Bovine Milk in Punjab, India: Spatial Variation and Risk Assessment to Human Health

Abstract: In the present study, gas chromatographic analysis of pesticide residues in bovine milk (n = 312) from Punjab, India, showed chlorpyrifos, DDT, and γ-HCH as the predominant contaminants. In addition, the presence of β-endosulfan, endosulfan suphate, cypermethrin, cyhalothrin, fenvalerate, deltamethrin, malathion, profenofos, and ethion was reported in milk samples. In this study, it was observed that 12 milk samples exceeded the maximum residue limits (MRLs) for γ-HCH (lindane), 18 for DDT and chlorpyrifos, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 34 publications
2
18
1
1
Order By: Relevance
“…These pesticides are sold under different brand names such as "Sarifos", "Yarifos", "Tricel". Pesticides such as these have been reported to exhibit a range of effects on both exposed people and the environment (Alcocer et al, 2000;Acker and Nogueira, 2012;Alves et al, 2012;Androutsopoulos et al, 2012;Ali et al, 2014;Mahamood et al, 2014;Bedi et al, 2015). This is an indication that the way pesticides are used in Sierra Leone can be hazardous to both the people exposed to pesticides and the environment.…”
Section: Types Of Pesticides Used In Sierra Leone Rice Fieldsmentioning
confidence: 93%
“…These pesticides are sold under different brand names such as "Sarifos", "Yarifos", "Tricel". Pesticides such as these have been reported to exhibit a range of effects on both exposed people and the environment (Alcocer et al, 2000;Acker and Nogueira, 2012;Alves et al, 2012;Androutsopoulos et al, 2012;Ali et al, 2014;Mahamood et al, 2014;Bedi et al, 2015). This is an indication that the way pesticides are used in Sierra Leone can be hazardous to both the people exposed to pesticides and the environment.…”
Section: Types Of Pesticides Used In Sierra Leone Rice Fieldsmentioning
confidence: 93%
“…but they were found lower than European maximum residues level (MRL= 8 µg /l). Similarly, Faouder et al (2007) and Bedi et al (2015) were reported that fipronil pesticide is used as flea and tick sprays for domestic animals hence it was excreted in milk.…”
Section: Discussionmentioning
confidence: 93%
“…This may be related to the imposition of ban/restriction on use of DDT and technical hexachlorocyclohexane (HCH) (α-, β-, γ-and δ-isomers) and increasing use of OPs and SPs groups as a replacement for persistent OCPs (Government of India, Ministry of Agriculture & Farmers Welfare, 2015) which is indicated by the occurrence of OPs and SPs even in human breast milk (Feo et al, 2012;Bedi et al, 2013). Similarly, the presence of OPs residues in bovine milk has already been reported by Pagliuca et al (2006) and Bedi et al (2015) and is mainly attributed to the ability of OPs to covalently link with milk proteins. Cheema et al (2004) have also reported the presence of chlorpyrifos in 6.7% of milk samples collected from Punjab (India), and concentrations in all of these samples exceeded MRL values.…”
Section: Discussionmentioning
confidence: 99%